Barriers to Professional Help-seeking for Distress and Potential Utility of a Mental Health App Components: Stakeholder Perspectives - Johnson, Jemimah A (Cureus, 2020)
Introduction A high prevalence of common mental disorders and the associated treatment gap, particularly in low and middle-income countries such as India, calls for novel mental health approaches with widespread reach. There is a need to enhance our understanding of the barriers experienced by distressed persons as well as to utilize these insights for breaking such barriers. Despite the rise in the use of technology-based solutions in the field of mental health, there is a dearth of app-based interventions that help in breaking barriers to seeking professional help for mental health concerns in distressed persons. The present study aimed at exploring the perspectives of distressed persons concerning barriers to seeking professional help for mental health concerns. It also sought to understand their perspectives on the perceived utility of proposed app components for breaking these barriers. Methods The study utilized a cross-sectional exploratory design. The sample included two groups of distressed participants who could be considered potential users (and thereby the stakeholders) of a mental health app under development for common mental health concerns: distressed treatment seekers (D-TS) and distressed non-treatment seekers (D-NTS). The D-TS group included 10 individuals (average age: 33 years; six men) with self-reported or clinician-reported depressive and anxiety symptoms at intake who were seeking help from mental health professionals. The D-NTS group included 10 distressed individuals (average age: 23 years; five men) who were recruited from the local community through an announcement. The announcement called for participants who were experiencing anxiety and low mood but had not yet sought help for their distress. A semistructured interview schedule was used to explore the nature of barriers encountered and the perceived utility of the content of the proposed app. The questions that aimed at understanding the perceived barriers were open-ended. The perceived utility of various components of the proposed app was explored via 11 items, with a 5-point Likert scale. Results Personal barriers frequently reported by both groups were doubts about treatment and fear of social consequences. The role of inadequate self-awareness about one’s mental health concerns as a barrier to reaching out for professional help was articulated more frequently by the D-TS group than the D-NTS group. Proposed app components such as self-assessment with individualized feedback, informative videos by mental health professionals, testimonials from mental health service users, and a platform for an online connection with a professional were rated as potentially useful in reducing barriers to professional help-seeking. Insights based on stakeholder perspectives have implications for further research and are being utilized for the development of a mental health app for common mental health concerns.